Study Protocol for “Exploring the safety and therapeutic potential of psilocybin in the treatment of anorexia nervosa in adolescents and young adults” - David Sjöström; Olea Schau Rybäck; Emma Claesdotter Knutsson; Petri Kajonius; Oskar Jensen Sondén; Per Carlbring; Johannes Björkstrand; Pouya Movahed Rad (PLoS ONE, 2026)
Background Anorexia nervosa (AN) is a severe psychiatric disorder with high morbidity, mortality, and relapse rates, most commonly emerging during adolescence. Despite specialized psychological and nutritional treatments, outcomes remain suboptimal, with high rates of relapse and chronicity. Psilocybin has been investigated with preliminary efficacy in other psychiatric conditions characterized by rigidity and treatment resistance, but clinical evidence in AN—particularly in adolescents—is limited. Objective The psiAN study aims to evaluate the safety, tolerability, and feasibility of psilocybin therapy combined with psychological support in adolescents and young adults with relapsing AN, while exploring clinical, experiential, and neurobiological correlates of change. Methods A phase IIa, open-label, randomized controlled trial enrolling individuals aged 16–35 years with DSM-5 AN and a history of relapse. Participants are randomized to receive either two administrations of psilocybin (25 mg) with manualized psychological support plus treatment as usual (TAU), or TAU alone. Primary outcomes focus on safety and tolerability, assessed through adverse events, psychiatric monitoring, and medical parameters measured from first dosing to primary endpoint. Secondary outcomes include change in eating disorder symptom severity, relapse composite measures, mood, well-being, personality traits from baseline to primary endpoint with follow-up to 12 months. Functional magnetic resonance imaging (fMRI) and peripheral brain-derived neurotrophic factor are included as exploratory mechanistic measures. fMRI will evaluate pre- to post-intervention changes in structural and functional connectivity and task-related responses during a simplified Monetary Incentive Delay task (MIDT) and a Calorie-Cue Task (CCT). ClinicalTrials.gov Identifier: NCT07169747. Ethics and dissemination The study follows Good Clinical Practice (GCP), the Declaration of Helsinki, and EU Clinical Trials Regulation requirements, with staged inclusion of adolescents (16–17-year-olds) after a safety board review of adult data (18–35-year-olds). This protocol was prepared with reference to the SPIRIT 2025 guidelines (Chan et al., 2025) to enhance transparency and inform future trials.